Characterization of the radial electric field and edge velocity shear in Wendelstein 7-X. (9th September 2020) - Carralero, D.; Estrada, T.; Windisch, T.; Velasco, J.L.; Alonso, J.A.; Beurskens, M.; Bozhenkov, S.; Damm, H.; Fuchert, G.; Gao, Y.; Jakubowski, M.; Nieman, H.; et al.
Abstract: In this work we present the first measurements obtained by the V-band Doppler reflectometer during the second operation phase of Wendelstein 7-X to discuss the influence in the velocity shear layer and the radial electric field, E r, of several plasma parameters such as magnetic configuration, rotational transform or degree of detachment. In the first place, we carry out a systematic characterization of the turbulence rotation velocity profile in order to describe the influence of density and heating power on E r under the four most frequent magnetic configurations. The | E r | value in the edge is found to increase with configurations featuring higher ι, although this does not apply for the high mirror configuration, KJM. As well, the E r value in the SOL and the velocity shear near the separatrix are found to display a clear dependence on heating power and density for all configurations. For a number of relevant cases, these results are assessed by comparing them to neoclassical predictions obtained from the codes DKES and KNOSOS, finding generally good agreement with experimental results. Finally, the evolution of E r at the edge is evaluated throughout the island-divertor detachment regime achieved for the first time in the 2018 campaign. After detachment, | E r | is reduced both at the SOL and edge, and the plasma column shrinks, with the shear layer seemingly moving radially inwards from the separatrix.